2019
DOI: 10.1101/528851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cassava planting material movement and grower behaviour in Zambia: implications for disease management

Abstract: 22Cassava is an important food crop for most small-holder growers across sub-Saharan Africa, where production is 23 largely limited by the presence of two viral diseases: cassava mosaic disease (CMD) and cassava brown streak 24 disease (CBSD), both propagated by a vector whitefly and via human-mediated movement of infected cassava 25 stems. Despite its importance, there is limited knowledge of growers' behaviour related to planting material 26 movement, as well as growers' perception and knowledge of cassava d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…p = 0) the disease spread across the landscape in a more “wavelike” pattern as expected from the thin-tailed dispersal kernel for the whitefly ( Shaw ( 1995 ), Appendix 2 Figure 6). However, when trade occurs via a market or central organisation the majority of transactions occur over a scale larger than our landscape (a square with sides 3.16 km), with around 70 % of transactions occur over a scale of 10-50 km ( Szyniszewska et al ( 2019 )). For more informal trade settings, with growers interacting with each other, a proximity-based kernel may be more appropriate ( McQuaid et al ( 2017b ), McQuaid et al ( 2017a ), though both of these were modelled over a larger landscape than ours).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…p = 0) the disease spread across the landscape in a more “wavelike” pattern as expected from the thin-tailed dispersal kernel for the whitefly ( Shaw ( 1995 ), Appendix 2 Figure 6). However, when trade occurs via a market or central organisation the majority of transactions occur over a scale larger than our landscape (a square with sides 3.16 km), with around 70 % of transactions occur over a scale of 10-50 km ( Szyniszewska et al ( 2019 )). For more informal trade settings, with growers interacting with each other, a proximity-based kernel may be more appropriate ( McQuaid et al ( 2017b ), McQuaid et al ( 2017a ), though both of these were modelled over a larger landscape than ours).…”
Section: Discussionmentioning
confidence: 99%
“…- will play an important role in determining participation. Indeed, surveys of cassava growers in Sub-Saharan Africa have found that such qualitative traits have a greater role in determining a grower’s preference than economic traits such as yield ( Szyniszewska et al ( 2019 ), Houngue et al ( 2019 )). These private preferences or perceptions of risk are intangible and though they are somewhat encapsulated with our “cost of control” parameter will vary from grower to grower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, stochasticity in the network or spatial structure highlights the importance of variability in the sourcing of cuttings. Here, modelling has shown that although re-use of supply from within a field, along with small-scale local exchanges, dominates in terms of seed and virus dispersal (Delaquis et al 2018 ; Szyniszewska et al 2019 ), the potential for larger-scale movement allows for rapid spread of virus across a landscape (McQuaid et al 2017b , 2017a ). Modelling of cassava viruses, transmitted both through a whitefly vector and infected cuttings, in this way requires the consideration not just of a network of interactions or a dispersal kernel, but of a spatially explicit network in combination with vector dispersal.…”
Section: Modelling Approaches For the Surveillance Detection And Cont...mentioning
confidence: 99%
“…Mapping cassava on a continental scale based on satellite imagery remains a major challenge. Cassava in sub-Saharan Africa dominates in small-holder farming systems with field sizes most frequently less than 1000 m 2 , which are often intercropped 16,17 . Field rotation, flexible harvesting times and variable planting seasons means there is no strongly defined pattern of field maturation in many areas.…”
Section: Background and Summarymentioning
confidence: 99%